Class II Division 2 malocclusion: a heritable pattern of small teeth in well-developed jaws - Peck, S; Peck, L; Kataja, M (The Angle orthodontist, 1998)
Angle's designation of the Class II Division 2 (II/2) malocclusion recognizes a unique combination of overbite, incisor retroclination, and sagittal discrepancy. A very severe II/2 phenotype, characterized by concealment of the mandibular incisors in occlusion, has been called Deckbiss in German, or cover-bite. In this report, the cover-bite malocclusion is studied to identify morphological factors associated with Angle's II/2 occlusal discrepancy. Selected X-ray cephalometric and odontometric measurements were recorded for 23 subjects (M14; F9) with II/2 cover-bite malocclusion. Data were compared with those from a control-reference sample of 537 individuals. Cephalometrically, the II/2 cover-bite sample showed a pattern of strong vertical posterior development of the mandible with forward-rotation and skeletofacial hypodivergence (p < 0.0001). Anteroposteriorly, the maxillomandibular dentoalveolar relationship was relatively normal, and the basal bone region of the mandibular corpus appeared significantly well developed anteriorly, accounting for excessive bony chin projection (p < 0.0001). Dentally, mesiodistal tooth diameters for the maxillary and mandibular incisors of the II/2 cover-bite sample were significantly smaller than those of the reference sample (p < 0.002), pointing to systematically reduced tooth-size as a trait associated with II/2 malocclusion. These findings of a characteristic pattern of heritable skeletal and tooth-size features in II/2 cover-bite malocclusion indicate the presence of strong genetic influences in the formation of Angle's II/2 deep-bite discrepancy.